Gender in Nordic Blue Economies. Initial networking results and future academic research - Svels, Kristina; Ounanian, Kristen; Gustavsson, Madeleine; Arias Schreiber, Milena (Nordic Council of Ministers, 2022)
The SAB network recognised two domains particularly relevant to countries in theArctic and High North region: (1) coastal, maritime, and marine-based activities,livelihoods, and industries; and (2) gender equality and women’s participation in thelabour market, governance and decision making. Nonetheless, the convergence ofthese two domains seldom materialised in our first review of work advancing thegender dimension in Nordic Blue Economies. The SAB’s initial analysis shows thatthere is still a clear need for Nordic countries to focus on gender issues in BlueEconomy agendas, especially beyond a traditional focus on fisheries.There are opportunities to learn from individual country contexts where genderresearch has been more prolific, e.g., Norway and Iceland, and a pressing need toreinforce gender research in e.g., Sweden, Finland, and Denmark. Other marinesectors in which to explore gender issues are aquaculture, offshore wind energy,shipping, marine tourism, blue foods and seabed mineral extraction. In the Nordicacademic gender research sphere, a need for capacity building due to generationaltransition has been evidenced; early career researchers require the support andengagement from more senior peers. Consequently, since the Blue Economyhighlights the great potential of an ocean economy that boosts innovation andemployment, gender research needs to be strengthened and receive sustainedsupport to ensure inclusiveness and equality across the maritime Nordic and Arcticregions.
Keywords: Gender; blue economy; Nordic; research network